Analysis of the growth and morpho-physiological performance of three cultivars of Colombian quinoa grown under a greenhouse - García-Parra, Miguel Ángel; Stechauner-Rohringer, Roman; García-Molano, Jose Francisco; Ortiz-Gonzalez, Daniel (Revista de Ciências Agroveterinárias, 2020)
Quinoa (Amaranthaceae) is a native pseudo-cereal produced throughout the South American zone, where it is used in the preparation of food and as a promising alternative for the colonization of edaphoclimatic areas affected by anthropic and natural factors. Among the main problems that affect crop production, we can include those related to growth, development and production, generated by limitations of adaptability of new cultivars in specific areas. For this reason, this research intended to analyze the growth and morph-physiological behavior of the cultivars of quinoa Blanca Soracá (BS), Blanca Jericó (BT), and Tunkahuan (T). The study was carried out in the greenhouse of the Faculty of Agricultural Sciences of the Cauca University (Colombia) located at 1880 m a.s.l. The analysis, allowed to recognize that the three cultivars of quinoa, show different times of phenological development, until harvest (138.25 ± 2.3 and 161 ± 1.1 days). The number of leaves, the height of plants, and the number of branches show adjustment of sigmoidal regression equations (R2 0.99 - 0.98) for the cultivars BJ and T, while total chlorophyll content was adjusted to cubic behavior (R2 0.90 - 0.89). The cultivars of quinoa express productive behaviors that are associated with early and late cycles, showing differences in the production and weight of seeds.